Structure and properties of exotic nano- and mesodiamonds with pentagonal symmetry - Tomilin, Felix N.; Pomogaev, Vladimir A.; Melchakova, Iuliia A; Artyushenko, Polina V.; Shubin, Aleksandr A.; Volodin, A. M.; Zilberberg, I. L.; Avramov, Pavel V. (Russian physics journal)
A comprehensive critical survey of structures of exotic nano-, meso- and microdiamonds with dodecahedral and icosahedral symmetry (N/MDPS) is presented. Due to their high dodecahedral or icosahedral symmetry, the unique complex atomic and electronic structure of N/MDPS leads to transport and mechanical properties very promising for photonic, quantum, and nanomechanical applications. To explain the nature of diamonds, theoretical models have been proposed based on the formation of twinned structures consisting of either 5 or 20 symmetrically equivalent tetrahedral and prismatic fragments of the face-centered cubic lattice with the formation of star-shaped or icosahedral clusters, respectively. It has been shown that these twinned nano- and mesodiamonds have limited dimensions due to accumulation of uncompensated structural stresses arising from the deviation of the angles between diamond facets from perfect 72 degrees in tetrahedral fragments of the face-centered cubic lattice to 70.5 degrees between five symmetrically equivalent twinned fragments.